THE OLD-CITY HALL PARK’S QUALITY BASED ON PERCEPTION AND USER ACTIVITY IN TEGAL CITY, CENTRAL JAVA - Pramudita Eka Aulia; Achmad Hadi Prabowo (International Journal on Livable Space, 2020)
The quality of the area is the vitality of a living and livable urban area and is present for urban space activities. The ancient traditions of creating community have been proven by having a place to meet. The expert said that this place is called a public space which provides the needs of the community for daily interaction from various social aspects and levels so that this place will become more meaningful for the city. Old-City Hall Park of Tegal is one of the three important Public Spaces that have an impression for local residents, and the other two are The City center square and Pancasila Park. There are three landmarks in the park that provide territorial marks for road users in the Pantura-province-street that have entered to Tegal City. However, during the time Tegal city developed, the Old City Hall Park often had regional problems where the parks is meaningless to local residents so that the ownership of a place decreased over time. Problems arise from the lack of visitors, park management that is not running well so it damages the Physical Attribute and street furniture of the park itself, and the emergence of illegal street vendors in the corners of the public spaces in the park area. This study uses a quantitative-qualitative mix-method. The purpose of this research is not far from solving the city park’s problem by analyzing the quality of the park in terms of the vitality of the area. The respondents used were 100 people. The analysis is carried out by identifying and searching for information on user activities, the physical conditions of the park, accessibility, and the meaning of city parks. The results of the study proved that after going through a survey of respondents' perceptions and field observations that the quality of the City Park was not sufficient, seen from the analysis of the physical environmental conditions of the park to support various types of activities, the respondent's perception of ownership of the park gradually disappeared along with the meaning of the place.